Extensive Abdominal Skin Necrosis Following Anterior Component Separation for a Large Ventral Hernia: A Case Report - Bakula, Branko; Sever, Marko; Karačić, Andrija; Bakula, Mirko; Grbavac, Martin; Romic, Ivan; Bogut, Ante; Zadro, Zvonko (Frontiers in Surgery, 2021)
Introduction: Hernia surgery is one of the most common operative procedures, performed in about 20 million cases per year all over the world, with ventral hernia accounting for about 30% of cases. Although the introduction of the anterior component separation (ACS) method, popularized primarily by Oscar Ramirez, has greatly facilitated closure of the largest abdominal wall defects, the 30-year experience in this technique has pointed to the risk of ischemic skin complications consequential to the major subcutaneous tissue dissection required. The aim of this case presentation of a patient who developed extensive necrosis of the abdominal wall skin following ACS procedure is to emphasize the importance of preserving rectus abdominis perforator blood vessels in order to preserve skin vitality. Case presentation:We present a case of a 58-year-old female patient with large recurrent ventral hernia. Hernial defect was closed by placing a large (30x25 cm) polypropylene mesh in the retro-rectus space using the Rives-Stoppa technique. To facilitate upper fascia closure anterior component separation according to Ramirez was performed bilaterally. The rectus perforator vessels were not preserved. Recovery of the patient was complicated with the extensive abdominal skin necrosis which was successfully treated with negative pressure wound therapy. Discussion:Transection of the musculocutaneous perforators of the epigastric artery during ACS results with compromised blood supply of the abdominal skin depending solely on the intercostal arteries. Skin ischemia following anterior component separation is a serious complication that can be presented with extensive necrosis associated with high morbidity and even mortality, while the treatment is long-lasting, complex and expensive. Considering the ever increasing prevalence of large ventral hernias, ever greater popularity of the anterior component separation technique, and the growing proportion of surgeons performing large ventral hernia operations independently, we think that the role of preserving perforated rectus vessels has not been emphasized enough. Therefore, the objective of this report is to stimulate surgeons to preserve skin vascularity and promote it in their routine in order to avoid these severe postoperative complications.